Optimasi Ekstraksi Antosianin Daun Jati (Tectona grandis linn.) dan Aktivitas Antioksidannya - Rahmadhani, Aintan; Hanwar, Dedi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aimed to optimize the extraction of anthocyanins and their antioxidant activity from teak leaves (Tectona grandis Linn.) using 1% ethanol-HCl solvent with varying ethanol concentrations. The method used is maceration with ethanol concentrations of 50%, 70% and 96%. The resulting extract was analyzed qualitatively through thin layer chromatography (TLC) tests and phytochemical and quantitative tests to determine anthocyanin levels and antioxidant activity. The results showed that 70% ethanol extract had the highest yield (18.5%), and all extracts met the yield requirements (>7.5%). The highest anthocyanin levels were found in 96% ethanol extract (26.022 mg/dL), with the best antioxidant activity (IC50 = 87.66 ppm). In conclusion, there is a linear relationship between antioxidant activity and anthocyanin levels, where the higher the ethanol concentration in the solvent, the more effective the extraction of anthocyanins and antioxidant activity from teak leaf samples. Keywords: Antioxidants, Anthocyanins, Teak Leaves, DPPH, Ethanol-HCl